Response of physically mature maize embryos to Fusarium verticillioides volatiles: An insight into lipoxygenase pathways. (March 2021) - Jacquat, Andrés G.; Usseglio, Virginia L.; Bohl, Luciana; Achimón, Fernanda; Porporatto, Carina; Areco, Vanessa A.; Pizzolitto, Romina P.; Zygadlo, Julio A.; Zunino, María P.; Dambolena, José S.
Abstract: At physiological maturity (PM), the maize grain shows a metabolic and gene transcriptional basal rate which is mainly related to the primary metabolism and cellular respiration, among other pathways. It is well known that adult plants are capable of responding to volatile organic compounds, but little evidence of this has been observed in seeds. The investigation of the induction in seeds of the oxylipin metabolism, a defense system, might reveal good agronomic implications, as the oxylipins play a primordial role in the constitutive and inducible chemical defenses. Thus, the objective of this study was to evaluate the response of maize grains at PM with respect to the oxylipin pathways, at the genetic, enzymatic and metabolic levels. We exposed grains to volatiles emitted by Fusarium verticillioides, a common fungal of maize, and to pure volatiles typical of the fungi, 1-octen-3-ol and 3-octanol. The results obtained showed that the volatiles emitted by these fungi are capable of increasing the expression of genes of the oxylipin pathways ( ZmLOX12, ZmAOS2 and ZmHPL genes) and the specific enzymatic activity of lipoxygenases (EULOX ), compared with the non-exposed grains. The 1-octen-3-ol compound, but not 3-octanol, was also able to stimulate EULOX . However, the profile of the volatile metabolites emitted by the induced grains did not correspond to that observed at the genetic and enzymatic levels. Future studies to measure different metabolites will be conducted in order to obtain a better understanding of induction. Taken together, the results found indicated that maize embryos at PM are capable of responding to the presence of volatile fungal compounds by increasing their basal oxylipin metabolism. This could lead to agronomic advances, such as the priming of seeds to improve performance against pathogens during germination. However, future studies also need to be conducted to evaluate this hypothesis. HIGHLIGHTS: The maize grains exposed to VOCs of F. verticillioides showed a significant increase in EULOX . The maize grains exposed to 1-octen-3-ol showed a significant increase in EULOX . The maize grains exposed to fungal VOCs revealed a increase of LOX AOS and HPL gene expression. There is an induction of the maize grains immune system by external application of bioactive VOCs. Future trials are needed to study a possible seed priming using fungal bioactive VOCs.